2016
DOI: 10.1159/000442285
|View full text |Cite
|
Sign up to set email alerts
|

Scapular Morphology and Forelimb Use during Foraging in Four Sympatric Cercopithecids

Abstract: Most investigations of primate scapular morphology use differences in locomotion to explain variation; less is known about how scapular geometry covaries with nonlocomotor behavior. We examined forelimb use during foraging in 4 cercopithecids ranging throughout the Ivory Coast's Tai Forest. During 5-min feeding bouts, we recorded the frequency individuals of Piliocolobus badius, Colobus polykomos, Cercocebus atys and Cercopithecus diana performed 5 forelimb behaviors involved in the acquisition and introductio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
11
1

Year Published

2016
2016
2020
2020

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 47 publications
8
11
1
Order By: Relevance
“…For human and domestic mammals, there is no specific term for this surface (Federative International Committee on Anatomical Terminology, ; ICVGAN, ), but it can be seen a surface for the origin of the m. teres major in the graphic representations of the scapula in the domestic dog (Evans & de Lahunta, ) and the human (Standring, ). Even in non‐human primates, this surface has already been previously described (Mivart, ), and current studies have indicated its presence such as in Lemur catta (Makungu, Groenewald, Plessis, Barrows, & Koeppel, ), cercopithecids (Dunham, Kane, & McGraw, ) and Saguinus leucopus (Vélez‐García, Monroy‐Cendales, & Castañeda‐Herrera, ). However, these are different to Tamandua, because this surface is not so great as to give origin to the m. subscapular, similar to what occurs in armadillos, where it is observed that this surface is wide but only at the level of the caudal angle (Acuña, Sidorkewicj, Popp, & Casanave, ; Miles, ; Olson, Womble, Thomas, Glenn, & Butcher, ; Taylor, ), which is considered by Monteiro and Abe () as an expansion of the infraspinous fossa in armadillos and developed due to the greater retraction required by the thoracic limb in order to dig—where a major part of the force is contributed by the m. teres major for their fossorial habits (Olson et al, ).…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…For human and domestic mammals, there is no specific term for this surface (Federative International Committee on Anatomical Terminology, ; ICVGAN, ), but it can be seen a surface for the origin of the m. teres major in the graphic representations of the scapula in the domestic dog (Evans & de Lahunta, ) and the human (Standring, ). Even in non‐human primates, this surface has already been previously described (Mivart, ), and current studies have indicated its presence such as in Lemur catta (Makungu, Groenewald, Plessis, Barrows, & Koeppel, ), cercopithecids (Dunham, Kane, & McGraw, ) and Saguinus leucopus (Vélez‐García, Monroy‐Cendales, & Castañeda‐Herrera, ). However, these are different to Tamandua, because this surface is not so great as to give origin to the m. subscapular, similar to what occurs in armadillos, where it is observed that this surface is wide but only at the level of the caudal angle (Acuña, Sidorkewicj, Popp, & Casanave, ; Miles, ; Olson, Womble, Thomas, Glenn, & Butcher, ; Taylor, ), which is considered by Monteiro and Abe () as an expansion of the infraspinous fossa in armadillos and developed due to the greater retraction required by the thoracic limb in order to dig—where a major part of the force is contributed by the m. teres major for their fossorial habits (Olson et al, ).…”
Section: Discussionsupporting
confidence: 59%
“…This surface has also been mistakenly considered part of the infraspinous fossa in M. tridactyla (Lima et al, 2013) , 1998;ICVGAN, 2017), but it can be seen a surface for the origin of the m. teres major in the graphic representations of the scapula in the domestic dog (Evans & de Lahunta, 2013) and the human (Standring, 2016). Even in non-human primates, this surface has already been previously described (Mivart, 1866), and current studies have indicated its presence such as in Lemur catta (Makungu, Groenewald, Plessis, Barrows, & Koeppel, 2015), cercopithecids (Dunham, Kane, & McGraw, 2015) and Saguinus leucopus (Vélez-García, Monroy-Cendales, & Castañeda-Herrera, 2019).…”
Section: Comparative Anatomysupporting
confidence: 55%
“…34,36 The origin of the teres major muscle from a specific bony feature of the scapula located on the caudal angle has been previously reported in S leucopus 4 and other primates. 40,41 The origin and insertion of the subscapularis muscle in S leucopus was similar to most other primates, 11,[22][23][24][27][28][29][30][31][32]37 humans, 10,14,26 and domestic mammals. 33,34,36 In Symphalangus syndactylus, the origin of this muscle can reach the caudal margin of the scapula as a variant, 31 which was constant in S leucopus.…”
Section: Comparative Myologymentioning
confidence: 91%
“…Hard and soft tissue characteristics generally associated with habitual locomotor modes are found in the limbs [Fleagle, 1976[Fleagle, , 1977, although non-locomotor activity also affects the postcrania [Dunham et al, 2015]. More recently, however, the advent of modern imaging techniques has allowed the examination of the internal portions of the cranium, including the labyrinth of the temporal bone, which includes the organ of balance [Spoor and Zonneveld, 1998].…”
Section: Introductionmentioning
confidence: 99%